2019
DOI: 10.1007/s10815-019-01634-3
|View full text |Cite
|
Sign up to set email alerts
|

The potential impact of tumor suppressor genes on human gametogenesis: a case-control study

Abstract: Purpose To study the incidence of tumor suppressor gene (TSG) mutations in men and women with impaired gametogenesis. Methods Gene association analyses were performed on blood samples in two distinct patient populations: males with idiopathic male infertility and females with unexplained diminished ovarian reserve (DOR). The male study group consisted of men with idiopathic azoospermia, oligozoospermia, asthenozoospermia, or teratozoospermia. Age-matched controls were men with normal semen analyses. The female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In one study, rs1883603, rs9434741, and rs17436816 polymorphisms of the CHD5 gene in endometriosis were examined, and it was found that rs9434741 was significantly associated with endometriosis 21 . Hershlag et al showed that the CHD5 c.*3198_*3199T, 3′‐UTR (rs538186680) mutation was significantly higher in infertile male specimens than in controls, so idiopathic causes of infertility may be associated with CHD5 disorders 22 . Much research has been done on various polymorphisms of the CHD5 gene, but so far, no study has been reported on the association of this gene with male infertility.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In one study, rs1883603, rs9434741, and rs17436816 polymorphisms of the CHD5 gene in endometriosis were examined, and it was found that rs9434741 was significantly associated with endometriosis 21 . Hershlag et al showed that the CHD5 c.*3198_*3199T, 3′‐UTR (rs538186680) mutation was significantly higher in infertile male specimens than in controls, so idiopathic causes of infertility may be associated with CHD5 disorders 22 . Much research has been done on various polymorphisms of the CHD5 gene, but so far, no study has been reported on the association of this gene with male infertility.…”
Section: Discussionmentioning
confidence: 99%
“…21 Hershlag et al showed that the CHD5 c.*3198_*3199T, 3 0 -UTR (rs538186680) mutation was significantly higher in infertile male specimens than in controls, so idiopathic causes of infertility may be associated with CHD5 disorders. 22 Much research has been done on various polymorphisms of the CHD5 gene, but so far, no study has been reported on the association of this gene with male infertility. The rs7513548 was significantly associated with diffuse melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variant of TP63 oncogene of uncertain clinical signi cance was identi ed in an individual with azoospermia clinic. Variants of the TP63 gene have been found to be associated with male infertility, including azoospermia, oligospermia, teratospermia, or asthenospermia (Hershlag et al 2019).…”
Section: Ad -Autosomal Dominant Inheritancementioning
confidence: 99%